Protein–alkaloid interaction in larval diet affects fitness in cactophilic Drosophila (Diptera: Drosophilidae) - Vrdoljak, Juan Esteban (2019)
Drosophila koepferae and Drosophila buzzatii are closely related cactophilic species with overlapping distributions in Andean regions. Both species exploit necrotic tissues, and whereas the former breeds and feeds mostly in columnar cacti of Trichocereus and Cereus genera rich in secondary metabolites, the latter primarily exploits a less toxic host of the genus Opuntia. Although secondary metabolites have been related to the pattern of host exploitation, the microbial community associated with necrosis of cacti could also play a key role in the nutrition and/or alkaloid tolerance of the flies. We investigated the interaction between natural alkaloids and a yeast-protein supplement on both fly species raised in each type of cactus separately. We found that alkaloids reduced viability in both species, whereas a diet poor in protein reduced it only in D. buzzatii, especially when raised in Trichocereus. Concerning fitness traits that are related to adulthood, the addition of yeasts had positive effects, whereas the absence of yeasts resulted in strong detrimental effects. We present evidence of antagonistic effects on fitness and an interaction between alkaloids and proteins when these components are present in the diets of the flies.